Correlation between self-concept according to Roy Adaptation Model with adherence to therapeutic regimen in hypertensive Outpatients who attended in one of hospitals affiliated to Urmia University of Medical Sciences and Health Services. - ashktorab, tahereh; Esmaeili Zabihi, roghaieh; banaderakhshan, homayon; Zayeri, farid; Zohari Anbuhi, sima (Advances in Nursing & Midwifery, 2012)
Abstract Background and aim Although drug treatment for hypertension is available, but just 30% hypertensive patients have controlled hypertension. Nowadays non adherence to recommended health regimen is accepted as a nursing diagnosis by American Nurses Association. The aim of this study was to determine correlation between self-concept (according to Roy Adaptation Model) and adherence to therapeutic health regimen in hypertensive outpatients who attended to one of hospitals affiliated to Uremia University of Medical Sciences and Health Services.